Blue-emitting nanocrystals with cubic shape and group IV metal fluoride passivation

By introducing Group IV metal fluoride shells into nanostructures, the problem of insufficient nanostructure performance in the prior art is solved, high quantum yield, narrow emission peak width and colloid stability are achieved, and the application performance of nanostructures is improved .

CN115244153BActive Publication Date: 2025-02-21SHOEI CHEM IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180018668.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-03
Filing Date
2021-03-03
Publication Date
2025-02-21
Estimated Expiration
2041-03-03

AI Technical Summary

Technical Problem

It is difficult to prepare nanostructures with high quantum yields, narrow emission peak widths, adjustable emission wavelengths and colloidal stability.

Method used

Using a nanostructure comprising a nanocrystal core and at least one shell, wherein at least one shell comprises a Group IV metal fluoride, such as ZrF4 or HfF4, is prepared by specific process methods such as mixing zinc, selenium and metal fluoride.

Benefits of technology

The high quantum yield of nanostructures, narrow emission peak width, adjustable emission wavelength and colloid stability are achieved, and the performance of nanostructures in electronic and optical devices is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115244153B_ABST
    Figure CN115244153B_ABST
Patent Text Reader

Abstract

The present disclosure relates to the field of nanotechnology. The present disclosure provides a method for preparing a nanostructure using a Group IV metal halide. The nanostructure has a high quantum yield, a narrow emission peak width, an adjustable emission wavelength, and colloidal stability. A nanostructure prepared using the method is also provided. In addition, a nanostructure film and a molded product containing the nanostructure are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of nanotechnology. The present disclosure provides a method for preparing a nanostructure using a Group IV metal fluoride, and also provides a nanostructure prepared using the method. The nanostructure has high quantum yield, narrow emission peak width, tunable emission wavelength and colloidal stability. In addition, a nanostructure film and a molded product containing the nanostructure are also provided. Background Art

[0002] Semiconductor nanostructures can be incorporated into various electronic and optical devices. The electrical and optical properties of such nanostructures vary, for example depending on their composition, shape and size. For example, the size-adjustable properties of semiconductor nanoparticles are of great interest for applications such as light emitting diodes (LEDs) and liquid crystal displays (LCDs). Highly luminescent nanostructures are particularly desirable for such applications.

[0003] The steric bulk of long-chain alkyl ligands can lead to insufficient ligand coverage on the surface of semiconductor nanocrystals due to packing limitations. Similarly, round particle surfaces exhibit steps, pits, and kinks that are difficult to passivate with ligands. When a potential is applied across the quantum dots, such unpassivated sites on the quantum dot surface can lead to mid-gap states that act as hole traps. Holes will accumulate at the HTL-QD interface, leading to increased operating voltage and irreversible electrochemical degradation.

[0004] It is necessary to prepare nanostructures with high quantum yield, narrow emission peak width, tunable emission wavelength and colloidal stability. Summary of the invention

[0005] The present disclosure provides a nanostructure comprising a nanocrystalline core and at least one shell, wherein the at least one shell comprises at least one metal fluoride as shown in formula (I):

[0006] MF4(I)

[0007] in:

[0008] M=Zr, Hf or Ti.

[0009] In some embodiments, the core comprises InP, InAs, ZnSe, ZnTe, or ZnSe 1-x Te x , where 0≤x<1.

[0010] In some embodiments, the core comprises ZnSe or ZnSe 1-x Te x , where 0≤x<1.

[0011] In some embodiments, at least one shell is selected from CdS, CdSe, CdO, CdTe, ZnS, ZnO, ZnSe, ZnTe, MgTe, GaAs, GaSb, GaN, HgO, HgS, HgSe, HgTe, InAs, InSb, InN, AlAs, AlN, AlSb, AlS, PbS, PbO, PbSe, PbTe, MgO, MgS, MgSe, MgTe, CuCl, Ge, Si, and alloys thereof.

[0012] In some embodiments, at least one shell comprises ZnSe or ZnS.

[0013] In some embodiments, the at least one metal fluoride is HfF4 or ZrF4.

[0014] In some embodiments, the molar ratio of at least one metal fluoride to zinc in the nanostructure is from about 1:1 to about 1:8.

[0015] In some embodiments, the nanostructure comprises:

[0016] (a) a core comprising ZnSe, at least one shell comprising ZnS and at least one shell comprising HfF4; or

[0017] (b) Containing ZnSe 1-x Te x A core wherein 0≤x<1, at least one shell comprising ZnSe, and at least one shell comprising ZnS, and at least one shell comprising HfF4.

[0018] In some embodiments, the nanostructures are quantum dots.

[0019] In some embodiments, the photoluminescence quantum yield of the nanostructures is from about 60% to about 100%.

[0020] In some embodiments, the nanostructures have a full width at half maximum of about 10 nm to about 40 nm.

[0021] In some embodiments, the nanostructure composition comprises:

[0022] (a) nanostructures as described herein; and

[0023] (b) at least one organic resin.

[0024] The present disclosure also provides a method for preparing a nanostructure, comprising:

[0025] (a) providing a nanocrystal core;

[0026] (b) optionally mixing the core of (a) with a zinc source and a selenium source to provide a core having a ZnSe shell;

[0027] (c) mixing the core in (a) or the core with a ZnSe shell in (b) with a zinc source, a sulfur source and at least one metal fluoride of formula (I):

[0028] MF4(I)

[0029] in:

[0030] M=Zr, Hf or Ti.

[0031] To provide the nanostructure.

[0032] In some embodiments, the core comprises InP, InAs, ZnSe, ZnTe, or ZnSe 1-x Te x , where 0≤x<1.

[0033] In some embodiments, the core comprises ZnSe or ZnSe 1-x Te x , where 0≤x<1.

[0034] In some embodiments, the zinc source in (b) is selected from diethylzinc, dimethylzinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or a mixture thereof.

[0035] In some embodiments, the zinc source in (c) is selected from diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate, or a mixture thereof.

[0036] In some embodiments, the selenium source in (b) is selected from trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octane selenol, 1-dodecane selenol, selenophene, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenourea, and combinations thereof.

[0037] In some embodiments, the sulfur source in (c) is selected from elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, and combinations thereof.

[0038] In some embodiments, the temperature in (b) is increased, decreased, or maintained between about 200°C and about 310°C.

[0039] In some embodiments, the temperature in (c) is increased, decreased, or maintained between about 280°C and about 310°C.

[0040] In some embodiments, the photoluminescence quantum yield of the nanostructures is from about 60% to about 100%.

[0041] In some embodiments, the nanostructures have a full width at half maximum of about 10 nm to about 40 nm.

[0042] The present disclosure also provides a lighting device, comprising:

[0043] (a) a first conductive layer;

[0044] (b) a second conductive layer; and

[0045] (c) an emissive layer, wherein the emissive layer comprises at least one population of nanostructures comprising a core and at least one shell, wherein at least one shell comprises a Group IV metal fluoride.

[0046] In some embodiments, the core of the nanostructure comprises InP, InAs, ZnSe, ZnTe, or ZnSe 1-x Te x , where 0≤x<1.

[0047] In some embodiments, the core of the nanostructure comprises ZnSe or ZnSe 1-x Te x , where 0≤x<1.

[0048] In some embodiments, at least one shell of the nanostructure is selected from CdS, CdSe, CdO, CdTe, ZnS, ZnO, ZnSe, ZnTe, MgTe, GaAs, GaSb, GaN, HgO, HgS, HgSe, HgTe, InAs, InSb, InN, AlAs, AlN, AlSb, AlS, PbS, PbO, PbSe, PbTe, MgO, MgS, MgSe, MgTe, CuCl, Ge, Si, and alloys thereof.

[0049] In some embodiments, at least one shell of the nanostructure comprises ZnSe or ZnS.

[0050] In some embodiments, the at least one metal fluoride of the nanostructure is HfF4 or ZrF4.

[0051] In some embodiments, the device is stable for at least 7 days when stored at room temperature.

[0052] In some embodiments, the device is stable for at least 14 days when stored at room temperature.

[0053] In some embodiments, the lighting device further comprises an electron transport layer.

[0054] In some embodiments, the lighting device is a light emitting diode.

[0055] In some embodiments, the first conductive layer comprises indium tin oxide, indium zinc oxide, tin dioxide, zinc oxide, magnesium, aluminum, aluminum-lithium, calcium, magnesium-indium, magnesium-silver, silver, gold, or mixtures thereof.

[0056] In some embodiments, the first conductive layer includes indium tin oxide.

[0057] In some embodiments, the second conductive layer includes indium tin oxide, indium zinc oxide, titanium dioxide, tin oxide, zinc sulfide, silver, or a mixture thereof.

[0058] In some embodiments, the second conductive layer comprises aluminum.

[0059] In some embodiments, the second conductive layer comprises gold.

[0060] In some embodiments, the lighting device further comprises a semiconducting polymer layer.

[0061] In some embodiments, the semiconducting polymer layer includes copper phthalocyanine, 4,4',4"-tris[(3-methylphenyl)phenylamino]triphenylamine (m-MTDATA), 4,4',4"-tris(diphenylamino)triphenylamine (TDATA), 4,4',4"-tris[2-naphthyl(phenyl)amino]triphenylamine (2T-NATA), polyaniline / dodecylbenzenesulfonic acid, poly(3,4-ethylenedioxythiophene) / polystyrenesulfonate (PEDOT / PSS), polyaniline / camphorsulfonic acid or polyaniline / poly(4-styrenesulfonate).

[0062] In some embodiments, the semiconducting polymer layer comprises PEDOT / PSS.

[0063] In some embodiments, the lighting device further comprises a first transmission layer.

[0064] In some embodiments, the first transport layer comprises N,N'-di(naphthalen-1-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl))diphenylamine)], or poly(9-vinylcarbazole).

[0065] In some embodiments, the first transport layer comprises N,N'-di(naphthalen-1-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 is a state density diagram that describes the states available to be occupied by the system, where the mid-gap trap states are denoted as “trap states.” Complete surface coverage of halide ions can reduce the mid-gap trap states, resulting in a better electronically balanced quantum dot.

[0067] Figure 2 It is a table comparing the solution quantum yield, maximum external quantum efficiency and device lifetime of control ZnSe quantum dots, ZnSe quantum dots containing only ZnF2 in the shell, ZnSe quantum dots containing only HfF4 in the shell and ZnSe quantum dots containing only ZrF4 in the shell.

[0068] Figure 3 is a transmission electron microscope (TEM) image showing a quasi-spherical morphology, which is typical of ZnSe / ZnS core / shell structured quantum dots.

[0069] Figure 4 is a TEM image showing the increased ratio of tetrahedral and cubic particles resulting from the synthesis of ZnSe / ZnS core / shell structured quantum dots using Hf4.

[0070] Figure 5 is a TEM image showing a quasi-spherical morphology, which is typical of ZnSeTe / ZnSe / ZnS core / shell / shell structured quantum dots.

[0071] Figure 6 is a TEM image showing the increased ratio of tetrahedral and cubic particles resulting from the synthesis of ZnSeTe / ZnSe / ZnS core / shell / shell structured quantum dots using Hf4.

[0072] Figure 7 is a scatter plot of external quantum efficiency versus brightness for devices prepared using quantum dots with standard ligands (■), ZrF4 ligands (◆), and HfF4 ligands (◆).

[0073] Figure 8is a scatter plot of voltage versus time for hole-only devices made using quantum dots made with standard ligands (●), ZrF4 ligands (■), and HfF4 ligands (◆). All devices had equal quantum dot thickness and were driven at a hole current density of 0.1J. DETAILED DESCRIPTION

[0074] definition

[0075] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those generally understood by those of ordinary skill in the art to which the invention belongs. The following definitions supplement the definitions in the prior art and are directed to the current application, and should not be attributed to any related or unrelated circumstances, such as any jointly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be used in the testing practices of the present invention, the present invention describes preferred materials and methods. Therefore, the terms used here are only used for the purpose of describing specific embodiments and are not intended to be limiting.

[0076] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and the like.

[0077] As used herein, the term "about" means that the value of a given quantity varies by ±10% of the stated value, for example, "about 100 nm" includes a size range from 90 nm to 110 nm (including the endpoint values).

[0078] "Nanostructure" is a structure with at least one size less than the region or characteristic size of about 500nm. In some embodiments, the nanostructure has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm. Typically, the region or characteristic size will be along the minimum axis of the structure. The example of this structure includes nanowires, nanorods, nanotubes, branched nanostructures, nano four needles, nano three needles, nano two needles, nanocrystals, nanodots, quantum dots, nanoparticles, etc. Nanostructure can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous or its combination. In some embodiments, each of the three dimensions of the nanostructure has a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.

[0079] When used in relation to a nanostructure, the term "heterostructure" refers to a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of the nanostructure comprises a first material type, while a second region of the nanostructure comprises a second material type. In certain embodiments, the nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material. Wherein the different material types are distributed radially around, for example, the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. A shell may, but need not, completely cover an adjacent material to be considered a shell or to cause the nanostructure to be considered a heterostructure; for example, a nanocrystal characterized by a core of one material being covered by an island of a second material is a heterostructure. In other embodiments, the different material types are distributed at different locations within the nanostructure; for example, along the major axis (long axis) of a nanowire or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure may comprise completely different materials or the different regions may comprise a base material (e.g., silicon) having different dopants or different concentrations of the same dopant.

[0080] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section perpendicular to a first axis of the nanostructure, where the first axis differs the most from the lengths of the second and third axes (the second and third axes being the two axes whose lengths are closest to being equal to each other). The first axis is not necessarily the longest axis of the nanostructure; for example, for a disc-shaped nanostructure, the cross section will be a substantially circular cross section perpendicular to the short longitudinal axis of the disc. If the cross section is not circular, the diameter is the average of the major and minor axes of the cross section. For elongated or high aspect ratio nanostructures, such as nanowires, the diameter is measured in a cross section perpendicular to the longest axis of the nanowire. For spherical nanostructures, the diameter is measured from one side to the other through the center of the sphere.

[0081] When used in relation to nanostructures, the term "crystalline" or "substantially crystalline" refers to the fact that the nanostructure generally exhibits long-range order in one or more dimensions of the structure. Those skilled in the art will appreciate that the term "long-range order" will depend on the absolute size of the particular nanostructure, since the ordering of a single crystal cannot extend beyond the boundaries of the crystal. In this case, "long-range order" will mean substantially order at least in most dimensions of the nanostructure. In some cases, the nanostructure may be provided with an oxide or other coating or may consist of a core and at least one shell. In this case, it is understood that the oxide, shell (one or more shells) or other coating may, but need not, exhibit such order (e.g., it may be amorphous, polycrystalline or other). In this case, the phrase "crystalline", "substantially crystalline", "substantially single crystal" or "single crystal" refers to the central core of the nanostructure (not including the coating or shell). The term "crystalline" or "substantially crystalline" as used herein is also intended to include structures containing various defects, stacking faults, atomic substitutions, etc., as long as the structure exhibits long-range order (e.g., the degree of order exceeds at least about 80% of the length of at least one axis of the nanostructure or its core). In addition, it should be understood that the interface between the core and the thickness of the outer portion of the nanostructure or the core and the thickness of the adjacent shell or the shell and the thickness of the second adjacent shell may contain non-crystalline regions and may even be amorphous. This does not prevent the nanostructure from being crystalline or substantially crystalline as defined in the present invention.

[0082] When used with respect to a nanostructure, the term "single crystalline" means that the nanostructure is substantially crystalline and consists essentially of a single crystal. When used with respect to a nanostructure heterostructure comprising a core and one or more shells, "single crystalline" means that the core is substantially crystalline and consists essentially of a single crystal.

[0083] "Nanocrystal" is a substantially monocrystalline nanostructure.Therefore, nanocrystal has at least one size less than the region or characteristic size of about 500nm.In some embodiments, the nanocrystal has a size less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.The term "nanocrystal" is intended to include a substantially monocrystalline nanostructure comprising various defects, stacking faults, atomic substitutions, etc., and a substantially monocrystalline nanostructure without these defects, stacking faults or substitutions.In the case of a nanocrystal heterostructure comprising a core and one or more shells, the core of the nanocrystal is typically substantially monocrystalline, but the shell (one or more) does not need to be like this.In some embodiments, each of the three-dimensional dimensions of the nanocrystal has a size less than about 500nm, less than about 200nm, less than about 100nm, less than about 50nm, less than about 20nm or less than about 10nm.

[0084] The term "quantum dot" (or "dot") refers to a nanocrystal that exhibits quantum confinement or exciton confinement. Quantum dots can be substantially homogeneous in material properties or can be heterogeneous in certain embodiments, for example comprising a core and at least one shell. The optical properties of quantum dots can be affected by their particle size, chemical composition, and / or surface composition, and can be determined by appropriate optical tests available in the art. The ability to customize the size of the nanocrystal (e.g., in the range of about 1 nm to about 15 nm) enables light emission coverage throughout the spectrum to provide great diversity in color rendering.

[0085] A "ligand" is a molecule capable of interacting (whether weakly or strongly) with one or more faces of a nanostructure, such as through covalent, ionic, van der Waals or other molecular interactions with the nanostructure surface.

[0086] "Photoluminescence quantum yield" is the ratio of photons emitted to photons absorbed, e.g., by a nanostructure or population of nanostructures. As is known in the art, quantum yield is typically determined by comparison methods using well-characterized standard samples with known quantum yield values.

[0087] As used herein, the term "monolayer" is a unit of measure of shell thickness derived from the bulk crystal structure of the shell material as the closest distance between the relevant lattice planes. For example, for a cubic lattice structure, the thickness of a monolayer is determined as the distance between adjacent lattice planes in the

[111] direction. For example, a cubic ZnSe monolayer corresponds to 0.33nm, while a cubic ZnS monolayer corresponds to a thickness of 0.31nm. The monolayer thickness of an alloy material can be determined from the alloy composition by Vegard's law.

[0088] As used in the present invention, the term "shell" refers to a material deposited on the core or previously deposited shells with the same or different composition, which is produced by a single deposition of the shell material. The exact shell thickness depends on the input and conversion of the material and precursor, and can be reported in nanometers or monolayers. As used in the present invention, "target shell thickness" refers to the expected shell thickness for calculating the required precursor amount. As used in the present invention, "actual shell thickness" refers to the actual deposition amount of the shell material after synthesis, which can be measured by methods known in the art. For example, the actual shell thickness can be measured by comparing the particle diameter determined by the TEM image of nanocrystals before and after the shell synthesis.

[0089] As used herein, the term "full width at half maximum" (FWHM) is a measure of the quantum dot size distribution. The emission spectrum of a quantum dot typically has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM and gives an idea of ​​the particle size distribution. A smaller FWHM corresponds to a narrower quantum dot nanocrystal size distribution. The FWHM also depends on the emission wavelength maximum.

[0090] "Peak emission wavelength" (PWL) is the wavelength at which the radiation emission spectrum of the light source reaches its maximum.

[0091] As used herein, the term "external quantum efficiency" (EQE) is the ratio of the number of photons emitted from a light emitting diode (LED) to the number of electrons that pass through the device. EQE measures how efficiently an LED converts electrons into photons and allows them to escape. EQE can be measured using the following formula: EQE = [injection efficiency] x [solid-state quantum yield] x [extraction efficiency]

[0092] in:

[0093] Injection efficiency = the fraction of electrons passing through the device that are injected into the active region;

[0094] Solid-state quantum yield = the fraction of all electron-hole recombination in the active region that are radiative and thus produce electrons; and

[0095] Extraction efficiency = the fraction of photons generated in the active region that escape from the device.

[0096] Unless expressly stated otherwise, the ranges listed herein are inclusive of the endpoints.

[0097] Various other terms are defined or otherwise described herein.

[0098] Core / shell nanoparticles are typically synthesized in a mixture of long alkyl chain compounds such as trioctylphosphine, lauric acid, and zinc oleate to coordinate and passivate the surface of the quantum dots. However, due to the limited packing density of the alkyl chains, complete surface passivation cannot be achieved, and therefore small ligands have been used for cooperative passivation. The present disclosure provides a method for incorporating Group IV metal fluorides such as zirconium fluoride and / or hafnium fluoride as a fluorine source into the shell growth reaction, which results in better ligand coverage of the surface and passivation of hole traps generated by dangling bonds. The resulting quantum dots are more stable in electroluminescent devices without seriously compromising the maximum external quantum efficiency. The resulting quantum dots maintain colloidal stability in non-polar solvents such as octane, which are preferably used for solution processing of the quantum dots into electroluminescent devices.

[0099] Nanostructure

[0100] In some embodiments, the present disclosure provides a nanostructure comprising a core and at least one shell, wherein the at least one shell comprises a Group IV metal fluoride.

[0101] In some embodiments, the present disclosure provides nanostructures comprising a core comprising zinc and at least one shell, wherein the at least one shell comprises zinc and a Group IV metal halide.

[0102] In some embodiments, the nanostructures are quantum dots.

[0103] Nanostructured compositions

[0104] In some embodiments, the present disclosure provides a nanostructure composition comprising:

[0105] (a) at least one population of nanostructures, the nanostructures comprising a core and at least one shell, wherein

[0106] wherein at least one shell comprises a Group IV metal fluoride; and

[0107] (b) at least one organic resin.

[0108] In some embodiments, the present disclosure provides a nanostructure composition comprising:

[0109] (a) at least one population of nanostructures comprising a core comprising zinc and at least one shell, wherein at least one shell comprises zinc and a Group IV metal halide; and

[0110] (b) at least one organic resin.

[0111] In some embodiments, the nanostructures are quantum dots.

[0112] Nanocrystalline core

[0113] In some embodiments, the nanostructures comprise InP, InAs, ZnSe, ZnTe, or ZnSe 1-x Te x In some embodiments, the nanostructure comprises a ZnSe core and a ZnS shell. In some embodiments, the nanostructure comprises a ZnSe core and a ZnS shell. 1-x Te x In some embodiments, the nanostructure is a ZnSe / ZnS core / shell nanostructure. In some embodiments, the nanostructure is a ZnSe core, a ZnSe shell, and a ZnS shell. 1-x Te x / ZnSe / ZnS core / shell nanostructures.

[0114] As used herein, the term "nucleation phase" refers to the formation of the core nucleus. As used herein, the term "growth phase" refers to the growth process in which additional inorganic material is added to the nanostructure.

[0115] The diameter of the nanocrystal core can be controlled by changing the amount of the precursor provided. The diameter of the nanocrystal can be measured using techniques known to those skilled in the art. In some embodiments, the diameter of the nanocrystal core is measured using a transmission electron microscope (TEM).

[0116] In some embodiments, the diameter of the nanocrystal core is about 1.0 nm to about 7.0 nm, about 1.0 nm to about 6.0 nm, about 1.0 nm to about 5.0 nm, about 1.0 nm to about 4.0 nm, about 1.0 nm to about 3.0 nm, about 1.0 nm to about 2.0 nm, about 2.0 nm to about 7.0 nm, about 2.0 nm to about 5.0 nm, about 2.0 nm to about 4.0 nm, about 2.0 nm to about 3.0 nm, about 3.0 nm to about 7.0 nm, about 3.0 nm to about 6.0 nm, about 3.0 nm to about 5.0 nm, about 3.0 nm to about 4.0 nm, about 4.0 nm to about 7.0 nm. About 4.0 nm and about 6.0 nm, about 4.0 nm and about 5.0 nm, about 5.0 nm and about 7.0 nm, about 5.0 nm and about 6.0 nm, or about 6.0 nm and about 7.0 nm. In some embodiments, the diameter of the nanocrystal core is from about 3.0 nm to about 6.0 nm.

[0117] In some embodiments, the nanocrystal core is doped with at least one metal ion or other element. Doping is the intentional introduction of impurities into the nanostructure in order to change the optical, electrical, chemical and / or magnetic properties of the nanostructure. Yim, K., et al., Scientific Reports 7:40907 (January 2017). In doping, very small amounts of metal ions are used, resulting in only minor deformations of the nanostructure lattice. In some embodiments, the concentration of the dopant is about 10 15 Atom / cm 3 and about 10 20 Atom / cm 3 between.

[0118] In some embodiments, the nanocrystalline core is doped with at least one metal ion or other element selected from lithium, boron, carbon, nitrogen, fluorine, sodium, aluminum, silicon, chlorine, potassium, scandium, selenium, titanium, vanadium, chromium, manganese, nickel, gallium, arsenic, palladium, gold, cadmium, indium, tin, antimony, lead, and combinations thereof. In some embodiments, the nanocrystalline core is doped with at least one metal ion or other element selected from indium, gallium, aluminum, selenium, titanium, tin, chlorine, fluorine, and combinations thereof.

[0119] In some embodiments, the nanocrystal core forms an alloy with at least one metal ion or other element. An alloy is a combination of at least two metals or a combination of at least one metal ion and at least one other element. When forming an alloy, a high concentration of metal ions or other elements is used, resulting in properties that are usually different from pure materials. In some embodiments, the concentration of metal ions or other elements alloyed therewith is about 0.1wt% to about 50wt%.

[0120] In some embodiments, the nanocrystalline core is alloyed with at least one metal or other element selected from magnesium, cadmium, mercury, sulfur, tellurium, and selenium. In some embodiments, the ZnSe nanocrystalline core is alloyed with tellurium.

[0121] In some embodiments, the cores are purified prior to depositing the shell. In some embodiments, the cores are filtered to remove precipitate from the core solution.

[0122] In some embodiments, the core is subjected to an acid etching step prior to depositing the shell.

[0123] In some embodiments, the diameter of the core is determined by measuring the lowest energy electronic transition using absorption spectroscopy and modeling the corresponding quantum dot size based on the quantum confinement principle. Quantum confinement in zero-dimensional nanocrystals (e.g., quantum dots) originates from the spatial confinement of electrons within the crystallite boundary. Once the diameter of the material has the same size as the de Broglie wavelength of the wave function, quantum confinement can be observed. The electronic and optical properties of nanoparticles are substantially different from those of bulk materials. When the constrained size is larger than the wavelength of the particle, the particle behaves as if it is free. During this state, due to the continuous energy state, the band gap remains at its original energy. However, when the constrained size is reduced and reaches a certain limit, usually at the nanoscale, the energy spectrum becomes discrete. As a result, the band gap becomes dependent on size.

[0124] Nanostructured shell

[0125] The shell can, for example, increase the quantum yield and / or stability of the nanostructure. In some embodiments, the core and shell comprise different materials. In some embodiments, the nanostructure comprises shells of different shell materials.

[0126] In some embodiments, a shell comprising a mixture of Group II and Group VI elements is deposited onto a core or core / shell structure. In some embodiments, the shell is deposited from a mixture of at least two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is deposited from a mixture of two of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is deposited from a mixture of three of a zinc source, a selenium source, a sulfur source, a tellurium source, and a cadmium source. In some embodiments, the shell is composed of: zinc and sulfur; zinc and selenium; zinc, sulfur and selenium; zinc and tellurium; zinc, tellurium and sulfur; zinc, tellurium and selenium; zinc, cadmium and sulfur; zinc, cadmium and selenium; cadmium and sulfur; cadmium and selenium; cadmium, selenium and sulfur; cadmium, zinc and sulfur; cadmium, zinc and selenium; or cadmium, zinc, sulfur and selenium.

[0127] In some embodiments, the at least one shell comprises CdS, CdSe, CdO, CdTe, ZnS, ZnO, ZnSe, ZnTe, MgTe, GaAs, GaSb, GaN, HgO, HgS, HgSe, HgTe, InAs, InSb, InN, AlAs, AlN, AlSb, AlS, PbS, PbO, PbSe, PbTe, MgO, MgS, MgSe, MgTe, CuCl, Ge, Si, or an alloy thereof. In some embodiments, the at least one shell comprises ZnSe. In some embodiments, the at least one shell comprises ZnS. In some embodiments, the at least one shell comprises a first shell comprising ZnSe and a second shell comprising ZnS.

[0128] In some embodiments, the shell comprises more than one monolayer of shell material. The number of monolayers is the average of all nanostructures; therefore, the number of monolayers in the shell can be a fraction. In some embodiments, the number of monolayers in the shell is 0.25 to 10, 0.25 to 8, 0.25 to 7, 0.25 to 6, 0.25 to 5, 0.25 to 4, 0.25 to 3, 0.25 to 2, 2 to 10, 2 to 8, 2 to 7, 2 to 6, 2 to 5, 2 to 4, 2 to 3, 3 to 10, 3 to 8, 3 to 7, 3 to 4, 4 to 10, 4 to 8, 4 to 7, 4 to 6, 4 to 5, 5 to 10, 5 to 8, 5 to 7, 5 to 6, 6 to 10, 6 to 8, 6 to 7, 7 to 10, 7 to 8 or 8 to 10. In some embodiments, the shell comprises 3 to 5 monolayers.

[0129] The thickness of each shell can be determined using techniques known to those skilled in the art. In some embodiments, the thickness of each shell is determined by comparing the average diameter of the nanostructures before and after adding each shell. In some embodiments, the average diameter of the nanostructures before and after adding each shell is determined by TEM.

[0130] In some embodiments, the thickness of each shell is from about 0.05 nm to about 3.5 nm, from about 0.05 nm to about 2 nm, from about 0.05 nm to about 0.9 nm, from about 0.05 nm to about 0.7 nm, from about 0.05 nm to about 0.5 nm, from about 0.05 nm to about 0.3 nm, from about 0.05 nm to about 0.1 nm, from about 0.1 nm to about 3.5 nm, from about 0.1 nm to about 0.9 nm, from about 0.1 nm to about 0.7 nm, from about 0.1 nm to about 0.5 nm, from about 0.1 nm to about 0.3 nm, From about 0.3nm to about 3.5nm, from about 0.3nm to about 0.9nm, from about 0.3nm to about 0.7nm, from about 0.3nm to about 0.5nm, from about 0.5nm to about 3.5nm, from about 0.5nm to about 2nm, from about 0.5nm to about 0.9nm, from about 0.5nm to about 0.7nm, from about 0.7nm to about 3.5nm, from about 0.7nm to about 2nm, from about 0.7nm to about 0.9nm, from about 0.9nm to about 3.5nm, from about 0.9nm to about 2nm, or from about 2nm to about 3.5nm.

[0131] Methods for preparing nanostructures containing Group IV fluoride passivation in the shell

[0132] In some embodiments, the present disclosure provides a method of preparing a nanostructure, comprising:

[0133] (a) providing a nanocrystal core;

[0134] (b) optionally mixing the core of (a) with a zinc source and a selenium source to provide a core having a ZnSe shell;

[0135] (c) mixing the core in (a) or the core with a ZnSe shell in (b) with a zinc source, a sulfur source and a Group IV fluoride;

[0136] To provide the nanostructure.

[0137] In some embodiments, the present disclosure provides a method of preparing a nanostructure, comprising:

[0138] (a) providing a nanocrystal core;

[0139] (b) mixing the core of (a) with a zinc source and a selenium source to provide a core having a ZnSe shell;

[0140] (c) mixing the core with the ZnSe shell in (b) with a zinc source, a sulfur source and a Group IV fluoride;

[0141] To provide the nanostructure.

[0142] In some embodiments, the present disclosure provides a method of preparing a nanostructure, comprising:

[0143] (a) providing a nanocrystal core;

[0144] (b) mixing the core of (a) with a zinc source, a sulfur source and a Group IV fluoride;

[0145] To provide the nanostructure.

[0146] In some embodiments, the nanocrystal core comprises ZnSe, ZnSe 1-x Te x , InP or InAs. In some embodiments, the nanocrystal core comprises ZnSe. In some embodiments, the nanocrystal core comprises ZnSe 1-x Te x .

[0147] In some embodiments, the zinc source is a dialkyl zinc compound. In some embodiments, the zinc source is a zinc carboxylate. In some embodiments, the zinc source is diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc caproate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or its mixture. In some embodiments, the zinc source is zinc dioleate, zinc caproate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or its mixture. In some embodiments, the zinc source is zinc dioleate. In some embodiments, the zinc source is zinc dioleate generated in situ.

[0148] In some embodiments, the selenium source is an alkyl-substituted selenourea. In some embodiments, the selenium source is phosphine selenide. In some embodiments, the selenium source is selected from trioctylphosphine selenide, tri (n-butyl) phosphine selenide, tri (sec-butyl) phosphine selenide, tri (tert-butyl) phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octane selenol, 1-dodecane selenol, selenol, elemental selenium, hydrogen selenide, bis (trimethylsilyl) selenide, selenourea and combinations thereof. In some embodiments, the selenium source is tri (n-butyl) phosphine selenide, tri (sec-butyl) phosphine selenide or tri (tert-butyl) phosphine selenide. In some embodiments, the selenium source is trioctylphosphine selenide.

[0149] In some embodiments, the sulfur source is selected from elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl)sulfide, trioctylphosphine sulfide and combinations thereof. In some embodiments, the sulfur source is alkyl-substituted zinc dithiocarbamate. In some embodiments, the sulfur source is octanethiol. In some embodiments, the sulfur source is tributylphosphine sulfide.

[0150] In some embodiments, the molar ratio of nanocrystalline cores to zinc source is 1:2 to 1:1000, 1:2 to 1:100, 1:2 to 1:50, 1:2 to 1:25, 1:2 to 1:15, 1:2 to 1:10, 1:2 to 1:5, 1:5 to 1:1000, 1:5 to 1:100, 1:5 to 1:25, 1:5 to 1:15, 1:10 to 1:15, 1:10 to 1:25, 1:15 to 1:100, 1:15 to 1:25, 1:25 to 1:100, 1:25 to 1:50, 1:50 to 1:100, or 1:100 to 1:1000.

[0151] In some embodiments, the zinc source is zinc dioleate. In some embodiments, the zinc source is zinc dioleate prepared in situ. In some embodiments, the molar ratio of the nanocrystalline core to zinc dioleate is 1:2 to 1:1000, 1:2 to 1:100, 1:2 to 1:50, 1:2 to 1:25, 1:2 to 1:15, 1:2 to 1:10, 1:2 to 1:5, 1:5 to 1:1000, 1:5 to 1:100, 1:5 to 1:25, 1:5 to 1:15, 1:10 to 1:15, 1:10 to 1:100, 1:10 to 1:25, 1:15 to 1:15, 1:15 to 1:100, 1:25 to 1:100, 1:25 to 1:50, 1:50 to 1:100, or 1:100 to 1:100. In some embodiments, the molar ratio of nanocrystalline core to zinc dioleate is 1:2 to 1:50. In some embodiments, the molar ratio of nanocrystalline core to zinc dioleate is 1:20 to 1:30.

[0152] In some embodiments, the molar ratio of the nanocrystalline core to the sulfur source is 1:2 to 1:1000, 1:2 to 1:100, 1:2 to 1:50, 1:2 to 1:25, 1:2 to 1:15, 1:2 to 1:10, 1:2 to 1:5, 1:5 to 1:1000, 1:5 to 1:100, 1:5 to 1:25, 1:5 to 1:15, 1:10 to 1:15, 1:10 to 1:25, 1:15 to 1:100, 1:15 to 1:25, 1:25 to 1:100, 1:25 to 1:50, 1:50 to 1:100, or 1:100 to 1:1000.

[0153] In some embodiments, after mixing the zinc source and the selenium source, the temperature of the reaction mixture is between 200° C. and 310° C., 200° C. and 280° C., 200° C. and 250° C., 200° C. and 220° C., 220° C. and 310° C., 220° C. and 280° C., 220° C. and 250° C., 250° C. and 310° C., 250° C. and 280° C., or 280° C. and 310° C. In some embodiments, the temperature of the reaction mixture in (d) is between 250° C. and 310° C.

[0154] In some embodiments, the time to reach the temperature after mixing the zinc source and the selenium source is 2 to 240 minutes, 2 to 200 minutes, 2 to 100 minutes, 2 to 60 minutes, 2 to 40 minutes, 5 to 240 minutes, 5 to 200 minutes, 5 to 100 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 240 minutes, 10 to 200 minutes, 10 to 60 minutes, 10 to 40 minutes, 40 to 200 minutes, 40 to 100 minutes, 40 to 60 minutes, 60 to 240 minutes, 60 to 100 minutes, 100 to 240 minutes, 100 to 200 minutes, or 200 to 240 minutes.

[0155] In some embodiments, the temperature after the zinc source and selenium source are mixed is maintained for 2 to 240 minutes, 2 to 200 minutes, 2 to 100 minutes, 2 to 60 minutes, 2 to 40 minutes, 5 to 240 minutes, 5 to 200 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 240 minutes, 10 to 200 minutes, 10 to 100 minutes, 10 to 40 minutes, 40 to 240 minutes, 40 to 100 minutes, 40 to 60 minutes, 60 to 200 minutes, 60 to 100 minutes, 100 to 240 minutes, 100 to 200 minutes, or 200 to 240 minutes. In some embodiments, after the core or core with a ZnSe shell is mixed with the zinc source, sulfur source and Group IV fluoride, the temperature of the reaction mixture is maintained for 30 to 120 minutes.

[0156] In some embodiments, the temperature after mixing the core or core with a ZnSe shell with a zinc source, a sulfur source, and a Group IV fluoride is 200° C. to 310° C., 200° C. to 280° C., 200° C. to 250° C., 200° C. to 220° C., 220° C. to 310° C., 220° C. to 280° C., 220° C. to 250° C., 250° C. to 310° C., 250° C. to 280° C., or 280° C. to 310° C. In some embodiments, the temperature in (f) is 250° C. to 100° C.

[0157] In some embodiments, the time to reach the temperature after mixing the core or core with a ZnSe shell with the zinc source, the sulfur source, and the Group IV fluoride is 2 to 240 minutes, 2 to 200 minutes, 2 to 100 minutes, 2 to 60 minutes, 2 to 40 minutes, 5 to 240 minutes, 5 to 200 minutes, 5 to 100 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 240 minutes, 10 to 200 minutes, 10 to 60 minutes, 10 to 40 minutes, 40 to 240 minutes, 40 to 100 minutes, 40 to 60 minutes, 60 to 240 minutes, 60 to 200 minutes, 60 to 100 minutes, 100 to 240 minutes, 100 and 200 minutes, or 200 and 240 minutes.

[0158] In some embodiments, the time to reach the temperature after mixing the core or the core with the ZnSe shell with the zinc source, the sulfur source, and the Group IV fluoride is 2 to 240 minutes, 2 to 200 minutes, 2 to 100 minutes, 2 to 60 minutes, 2 to 40 minutes, 5 to 240 minutes, 5 to 200 minutes, 5 to 100 minutes, 5 to 60 minutes, 5 to 40 minutes, 10 to 240 minutes, 10 to 200 minutes, 10 to 60 minutes, 10 to 40 minutes, 40 to 240 minutes, 40 to 100 minutes, 40 to 60 minutes, 60 to 240 minutes, 60 to 200 minutes, 60 to 100 minutes, 100 to 240 minutes, 100 to 200 minutes, or 200 to 240 minutes.

[0159] In some embodiments, the number of monolayers in the ZnSe shell is 0.25 to 10, 0.25 to 8, 0.25 to 7, 0.25 to 6, 0.25 to 5, 0.25 to 4, 0.25 to 3, 0.25 to 2, 2 to 10, 2 to 8, 2 to 7, 2 to 6, 2 to 5, 2 to 4, 2 to 3, 3 to 10, 3 to 8, 3 to 7, 3 to 4, 4 to 10, 4 to 8, 4 to 7, 4 to 5, 5 to 10, 5 to 8, 5 to 7, 5 to 6, 6 to 10, 6 to 8, 6 to 7, 7 to 10, 7 to 8, or 8 to 10. In some embodiments, the ZnSe shell comprises 2 to 6 monolayers. In some embodiments, the ZnSe shell comprises 3 to 5 monolayers.

[0160] In some embodiments, the ZnSe monolayer has a thickness of about 0.328 nm.

[0161] In some embodiments, the thickness of the ZnSe shell is 0.08nm to 3.5nm, 0.08nm to 2nm, 0.08nm to 0.9nm, 0.08nm to 0.7nm, 0.08nm to 0.5nm, 0.08nm to 0.5nm, 0.2nm to 3.5nm, 0.2nm to 2nm, 0.2nm to 0.9nm, 0.2nm to 0.5nm, 0.5nm to 3.5nm, 0.5nm to 2nm, 0.5nm to 0.9nm, 0.7nm to 3.5nm, 0.7nm to 2nm, 0.7nm to 0.9nm, 0.9nm to 3.5nm, 0.9nm to 2nm, or 2nm to 3.5nm.

[0162] In some embodiments, the number of monolayers in the ZnS shell is between 0.25 to 10, 0.25 to 8, 0.25 to 7, 0.25 to 6, 0.25 to 5, 0.25 to 4, 0.25 to 3, 0.25 to 2, 2 to 10, 2 to 8, 2 to 7, 2 to 6, 2 to 5, 2 to 4, 2 to 3, 3 to 10, 3 to 8, 3 to 7, 3 to 4, 4 to 10, 4 to 8, 4 to 7, 4 to 6, 4 to 5, 5 to 10, 5 to 8, 5 to 7, 6 to 10, 6 to 8, 6 to 7, 7 to 10, 7 to 8, or 8 to 10. In some embodiments, the ZnS shell comprises 2-12 monolayers. In some embodiments, the ZnS shell comprises 4-6 monolayers.

[0163] In some embodiments, the ZnS monolayer has a thickness of about 0.31 nm.

[0164] In some embodiments, the thickness of the ZnS shell is between 0.08nm and 3.5nm, 0.08nm and 2nm, 0.08nm and 0.9nm, 0.08nm and 0.7nm, 0.08nm and 0.5nm, 0.08nm and 0.5nm, 0.2nm and 3.5nm, 0.2nm and 2nm, 0.2nm and 0.9nm, 0.2nm and 0.5nm, 0.5nm and 3.5nm, 0.5nm and 2nm, 0.5nm and 0.9nm, 0.7nm and 3.5nm, 0.7nm and 2nm, 0.7nm and 0.9nm, 0.9nm and 3.5nm, 0.9nm and 2nm, or 2nm and 3.5nm.

[0165] Group IV metal fluorides

[0166] The present disclosure provides a method of producing a nanostructure, the nanostructure comprising a core containing nanocrystals and at least one shell disposed on the core, wherein at least one shell comprises at least one Group IV metal fluoride. In some embodiments, the nanostructure comprises a core containing nanocrystals and at least two shells disposed on the core, wherein at least one shell comprises at least one Group IV metal fluoride. In some embodiments, the nanostructure comprises a core containing nanocrystals and at least two shells disposed on the core, wherein at least two shells comprise at least one Group IV metal fluoride.

[0167] In some embodiments, the at least one shell comprises 1, 2, or 3 Group IV metal fluorides. In some embodiments, the at least one shell comprises 1 Group IV metal fluoride. In some embodiments, the at least one shell comprises 2 Group IV metal fluorides. In some embodiments, the at least one shell comprises 3 Group IV metal fluorides.

[0168] In some embodiments, the Group IV metal fluoride has formula (I):

[0169] MF4(I)

[0170] in:

[0171] M=Zr, Hf or Ti.

[0172] In some embodiments, the Group IV metal fluoride is selected from ZrF4, HfF4, and TiF4. In some embodiments, the Group IV metal fluoride is ZrF4. In some embodiments, the Group IV metal fluoride is HfF4.

[0173] Concentration of Group IV metal fluoride

[0174] The concentration of the at least one Group IV metal fluoride in the nanostructure can be determined by optical density (OD) measurement. OD can be measured at 450 nm using a cuvette with a 1 cm path length. For a nanostructure with OD 450= 1.5 100 μL nanostructures, the concentration of the at least one Group IV metal fluoride in the solution is about 0.01 mM to about 40 mM, about 0.01 mM to about 20 mM, about 0.01 mM to about 10 mM, about 0.01 mM to about 5 mM, about 0.01 mM to about 2.5 mM, about 0.01 mM to about 1.5 mM, about 0.01 mM to about 0.5 mM, about 0.01 mM to about 0. 25mM, about 0.25mM to about 40mM, about 0.25mM to about 20mM, about 0.25mM to about 5mM, about 0.25mM to about 2.5mM, about 0.25mM to about 1.5mM, about 0.25mM to about 1.5mM, about 0.25mM to about 1mM, about 0.25mM to about 0.5mM, 0.25mM to about 0.25mM, about 0.5mM to about 40mM, about 0.5mM to about 20mM, about 0.5mM to about 10mM, about 0.5mM to about 2.5mM, about 0.5mM to about 1.5mM, about 0.5mM to about 1mM, about 1mM to about 40mM, about 1mM to about 10mM, about 1mM to about 5mM, about 1mM to about 2.5mM, about 1mM to about 1.5mM, about 1.5mM to about 40mM, about 1.5mM to about 20mM, about 1.5 mM to about 10 mM, about 1.5 mM to about 5 mM, about 1.5 mM to about 2.5 mM, about 2.5 mM to about 40 mM, about 2.5 mM to about 20 mM, about 2.5 mM to about 10 mM, about 5 mM to about 40 mM, about 5 mM to about 20 mM, about 5 mM to about 10 mM, about 10 mM to about 40 mM, about 10 mM to about 20 mM, or about 20 mM to about 40 mM. For OD 450 = 1.5 in 100 μL of nanostructures, the concentration of the at least one metal fluoride is between about 1 mM and about 2.5 mM.

[0175] Ratio of Group IV metal fluoride to zinc-containing core

[0176] In some embodiments, the molar ratio of the at least one Group IV metal fluoride to the core comprising zinc is between about 1:1 to about 8:1, about 1:1 to about 7:1, 1:1 to about 6:1, about 1:1 to about 5:1, about 1:1 to about 4:1, about 1:1 to about 3:1, about 2:1 to about 7:1, about 2:1 to about 7:1, about 2:1 to about 5:1, about 2:1 to about 4:1, about 3:1 to about 7:1, about 3:1 to about 6:1, about 3:1 to about 5:1, about 3:1 to about 4:1, about 4:1 to about 7:1, about 4:1 to about 6:1, about 4:1 to about 5:1, about 5:1 to about 8:1, about 5:1 to about 7:1, about 5:1 to about 6:1, about 6:1 to about 8:1, about 6:1 to about 7:1, or about 7:1 to about 8:1. In some embodiments, the molar ratio of the at least one Group IV metal fluoride to the zinc core is between about 1:1 to about 3:1.

[0177] Core / shell nanostructures

[0178] In some embodiments, the core / shell nanostructure is a ZnSe / ZnS structure. In some embodiments, the core / shell nanostructure is a ZnSe 1-x Te x / ZnSe / ZnS nanostructure. In some embodiments, the core / shell nanostructure is a ZnSe / ZnS nanostructure comprising HfF4 in the ZnS shell. In some embodiments, the core / shell nanostructure is a ZnSe / ZnS nanostructure comprising ZrF4 in the ZnS shell. In some embodiments, the core / shell nanostructure is a ZnSe / ZnS nanostructure 1-x Te x / ZnSe / ZnS nanostructures containing HfF4 in the ZnS shell.

[0179] Solvents

[0180] In some embodiments, the method of producing a nanostructure comprising a zinc core and at least two shells, wherein the at least two shells comprise zinc, further comprises a solvent.

[0181] In some embodiments, the solvent is selected from the group consisting of chloroform, acetone, hexane, heptane, butanone, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, 1,4-butanediol diacetate, diethylene glycol monobutyl ether acetate, ethylene glycol monobutyl ether acetate, triacetin, heptyl acetate, hexyl acetate, amyl acetate, butyl acetate, ethyl acetate, diethylene glycol butyl methyl ether, diethylene glycol monobutyl ether, di(propylene glycol) dimethyl ether, diethylene glycol ethyl methyl ether, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, methyl ethyl ketone, methyl isobutyl ketone, monomethyl ether glycol ester, γ-butyrolactone, methyl acetate-3-ethyl ether, butyl carbitol, butyl carbitol acetate, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, cyclohexane, toluene, xylene, isopropanol, and combinations thereof. In some embodiments, the solvent is hexane, heptane, toluene, or chloroform.

[0182] Improved properties of nanostructures

[0183] In some embodiments, the core / shell nanostructures prepared using the methods described herein exhibit high photoluminescence quantum yields. In some embodiments, the photoluminescence quantum yield of the core / shell nanostructures is 60% to 100%, 60% to 95%, 60% to 90%, 60% to 85%, 60% to 80%, 60% to 70%, 70% to 100%, 70% to 95%, 70% to 90%, 70% to 85%, 70% to 80%, 80% to 100%, 80% to 95%, 80% to 90%, 80% to 85%, 85% to 100%, 85% to 90%, 90% to 100%, 90% to 95%, or 95% to 100%. In some embodiments, the photoluminescence quantum yield of the core / shell nanostructures prepared using the methods described herein is 60% to 80%.

[0184] The photoluminescence spectrum of the core / shell nanostructures prepared using the methods described herein can cover substantially any desired portion of the spectrum. In some embodiments, the emission maximum of the photoluminescence spectrum of the core / shell nanostructure is 300nm to 750nm, 300nm to 650nm, 300nm to 550nm, 300nm to 450nm, 450nm to 750nm, 450nm to 650nm, 450nm to 550nm, 450nm to 650nm, 450nm to 550nm, 550nm to 750nm, 550nm to 650nm, or 650nm to 750nm. In some embodiments, the emission maximum of the photoluminescence spectrum of the core / shell nanostructure is 500nm to 550nm. In some embodiments, the emission maximum of the photoluminescence spectrum of the core / shell nanostructure prepared using the methods described herein is 430nm to 460nm.

[0185] The size distribution of the core / shell nanostructures prepared using the methods described herein can be relatively narrow. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the population or core / shell nanostructures prepared using the methods described herein is 10nm to 60nm, 10nm to 40nm, 10nm to 30nm, 10nm to 20nm, 20nm to 60nm, 20nm to 40nm, 20nm to 30nm, 30nm to 60nm, 30nm to 40nm, or 40nm to 60nm. In some embodiments, the full width at half maximum of the photoluminescence spectrum of the population or core / shell nanostructures prepared using the methods described herein is 10nm to 40nm.

[0186] In some embodiments, the nanostructures of the present invention have a cubic shape. The shape of the nanostructure can be determined by visual inspection. In some embodiments, the cubic shape of the nanostructure is observed by visual inspection of a TEM image.

[0187] In some embodiments, a population of nanostructures having a cubic shape is a population in which at least 75%, at least 80%, at least 85%, at least 90%, or at least 95% of the nanostructures have a cubic shape. In some embodiments, a population of nanostructures having a cubic shape is a population in which at least 85% of the nanostructures have a cubic shape.

[0188] Nanostructured thin films

[0189] In some embodiments, the core / shell nanostructures prepared by the methods described herein are incorporated into nanostructured films. In some embodiments, the nanostructured films are incorporated into quantum dot enhanced films (QDEFs).

[0190] In some embodiments, the present disclosure provides a nanostructured film comprising:

[0191] (a) at least one population of nanostructures, the nanostructures comprising a core and at least one shell, wherein

[0192] wherein at least one shell comprises a Group IV metal fluoride; and

[0193] (b) at least one organic resin.

[0194] In some embodiments, the nanostructures are quantum dots.

[0195] In some embodiments, the present disclosure provides a nanostructured film comprising:

[0196] (a) at least one population of nanostructures comprising a core comprising zinc and at least one shell, wherein at least one shell comprises zinc and a Group IV metal fluoride; and

[0197] (b) at least one organic resin.

[0198] In some embodiments, the nanostructures are quantum dots.

[0199] In some embodiments, the core / shell nanostructure is embedded in a matrix. As used herein, the term "embedded" is used to indicate that the nanostructure is encapsulated or wrapped in a matrix material that constitutes the main component of the matrix. In some embodiments, the nanostructure is uniformly distributed throughout the matrix material. In some embodiments, the nanostructure is distributed according to a specific uniformity distribution function of the application.

[0200] In some embodiments, the nanostructures may include a uniform population having a size that emits in the blue visible wavelength spectrum, the green visible wavelength spectrum, or the red visible wavelength spectrum. In some embodiments, the nanostructures may include a first population of nanostructures having a size that emits in the blue visible wavelength spectrum, a second population of nanostructures having a size that emits in the green visible wavelength spectrum, and a third population of nanostructures having a size that emits in the red visible wavelength spectrum.

[0201] The matrix material can be any suitable host matrix material capable of accommodating the nanostructure. Suitable matrix materials can be chemically and optically compatible with the nanostructure and any surrounding packaging materials or layers for applying the nanostructure film to the device. Suitable matrix materials can include non-yellowing optical materials that are transparent to both primary and secondary light, thereby allowing both primary and secondary light to be transmitted through the matrix material. Matrix materials can include polymers and organic and inorganic oxides. Suitable polymers for matrix materials can be any polymers known to those of ordinary skill in the art that can be used for this purpose. Polymers can be substantially translucent or substantially transparent. The matrix material may include, but is not limited to, epoxy resins, acrylates, norbornene, polyethylene, poly(vinyl butyral): poly(vinyl acetate), polyurea, polyurethane; silicones and silicone derivatives, including but not limited to aminosilicones (AMS), polyphenylmethylsiloxanes, polyphenylalkylsiloxanes, polydiphenylsiloxanes, polydialkylsiloxanes, silsesquioxanes, fluorinated silicones, and vinyl and hydride substituted silicones; acrylic polymers and copolymers formed from monomers including but not limited to methyl methacrylate, butyl methacrylate, and lauryl methacrylate; styrene-based polymers, such as polystyrene, aminopolystyrene (APS), and poly(acrylonitrile vinyl styrene) (AES); polymers crosslinked with difunctional monomers, such as divinylbenzene; crosslinking agents suitable for crosslinking ligand materials, epoxides combined with ligand amines (such as APS or polyethyleneimine ligand amines) to form epoxy groups, etc.

[0202] In some embodiments, the matrix material includes scattering microbeads, such as TiO2 microbeads, ZnS microbeads, or glass microbeads, which can improve the light conversion efficiency of the nanostructure film. In some embodiments, the matrix material can include a light blocking element.

[0203] In some embodiments, the matrix material can have low oxygen and moisture permeability, exhibit high light stability and chemical stability, exhibit a favorable refractive index, and adhere to the outer surface of the nanostructure, thereby providing an airtight seal to protect the nanostructure. In another embodiment, the matrix material can be cured with UV or thermal curing methods to facilitate roll-to-roll processing.

[0204] In some embodiments, the nanostructure film can be formed by mixing the nanostructures in a polymer (e.g., a photoresist) and casting the nanostructure-polymer mixture on a substrate, mixing the nanostructures with monomers and polymerizing them together, mixing the nanostructures in a sol-gel to form an oxide, or any other method known to those skilled in the art.

[0205] In some embodiments, the formation of the nanostructured film may include a film extrusion process. The film extrusion method may include forming a uniform mixture of a core / shell nanostructure of a matrix material and a barrier layer coating, such as a nanostructure functionalized with a Group IV metal fluoride, and introducing the uniform mixture into a top mounted feed hopper that feeds into an extruder. In some embodiments, the uniform mixture may be in the form of pellets. The film extrusion method may further include extruding the nanostructured film from a slit die and passing the extruded nanostructured film through a cooling roller. In some embodiments, the thickness of the extruded nanostructured film may be less than about 75 μm, for example, in the range of about 70 μm to about 40 μm, about 65 μm to about 40 μm, about 60 μm to about 40 μm, or about 50 μm to about 40 μm. In some embodiments, the thickness of the nanostructured film is less than about 10 μm. In some embodiments, the formation of the nanostructured film may optionally include a secondary process followed by a film extrusion process. The second process may include processes such as coextrusion, thermoforming, vacuum forming, plasma treatment, molding and / or embossing to provide texture to the top surface of the nanostructure film layer. Textured top surface nanostructure film can help improve the nanostructure film's, for example, defined light diffusion properties and / or defined angle light emission properties.

[0206] Quantum dots on glass LCD displays

[0207] In some embodiments, the nanostructure film is incorporated into quantum dots on a glass LCD display device. The LCD display device may include a nanostructure film formed directly on a light guide plate (LGP) without an intermediate substrate or barrier layer. In some embodiments, the nanostructure film may be a thin film. In some embodiments, the nanostructure film may have a thickness of 500 μm or less, 100 μm or less, or 50 μm or less. In some embodiments, the nanostructure film is a thin film having a thickness of about 15 μm or less.

[0208] The LGP may include an optical cavity having one or more sides (including at least the top side) comprising glass. Glass provides excellent tolerance to impurities including moisture and air. In addition, glass can be formed into a thin substrate while maintaining structural rigidity. Therefore, the LGP may be formed at least in part from a glass surface to provide a substrate with sufficient barrier and structural properties.

[0209] In some embodiments, a nanostructure film can be formed on an LGP. In some embodiments, the nanostructure film includes a nanostructure group embedded in a matrix material such as a resin. The nanostructure film can be formed on an LGP by any method known in the art, such as wet coating, painting, spin coating, or screen printing. After deposition, the resin of the nanostructure film can be cured. In some embodiments, the resin of one or more nanostructure films can be partially cured, further processed, and then finally cured. The nanostructure film can be deposited as a layer or as a separate layer, and the separate layer can include different properties. The width and height of the nanostructure film can be any desired size, depending on the size of the viewing panel of the display device. For example, the nanostructure film can have a relatively small surface area in a small display device embodiment such as a watch and a phone, or the nanostructure film can have a large surface area in a large display device embodiment such as a television and a computer monitor.

[0210] In some embodiments, an optically transparent substrate is formed on the nanostructure film by any method known in the art, such as vacuum deposition, vapor deposition, etc. The optically transparent substrate may be configured to provide an environmental seal to the lower layer and / or structure of the nanostructure film. In some embodiments, a light blocking element may be included in the optically transparent substrate. In some embodiments, the light blocking element may be included in a second polarizing filter, which may be located between the substrate and the nanostructure film. In some embodiments, the light blocking element may be a dichroic filter, which may, for example, reflect primary light (e.g., blue light, UV light, or a combination of UV light and blue light) while transmitting secondary light. The light blocking element may include a specific UV filter component to remove any unconverted UV light from the red and green sub-pixels, and / or UV light from the blue sub-pixel.

[0211] On-Chip and Near-Chip Placement of Quantum Dots

[0212] In some embodiments, the nanostructures are incorporated into the display device by placement "on chip". As used herein, "on chip" means that the nanostructures are placed in the LED cup. In some embodiments, the nanostructures are dissolved in a resin or fluid to fill the LED cup.

[0213] In some embodiments, the nanostructures are incorporated into the display device by "near-chip" placement. As used herein, "near-chip" refers to coating the top surface of the LED component with the nanostructures so that the exiting light passes through the nanostructure film.

[0214] Display device with nanostructured color conversion layer

[0215] In some embodiments, the present invention provides a display device comprising:

[0216] (a) a display panel for emitting a first light;

[0217] (b) a backlight unit configured to provide the first light to the display panel; and

[0218] (c) A color filter including at least one pixel region including a color conversion layer.

[0219] In some embodiments, the color filter includes at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 pixel areas. In some embodiments, when blue light is incident on the color filter, red light, white light, green light, and / or blue light can be emitted through the pixel areas, respectively. In some embodiments, the color filter is described in U.S. Patent Application Publication No. 2017 / 153366, which is incorporated herein by reference in its entirety.

[0220] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer includes nanostructures described herein that are configured to convert incident light to light of a first color. In some embodiments, the color conversion layer includes nanostructures described herein that are configured to convert incident light to blue light.

[0221] In some embodiments, the display device includes 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 color conversion layers. In some embodiments, the display device includes 1 color conversion layer including the nanostructures described herein. In some embodiments, the display device includes 2 color conversion layers including the nanostructures described herein. In some embodiments, the display device includes 3 color conversion layers including the nanostructures described herein. In some embodiments, the display device includes 4 color conversion layers including the nanostructures described herein. In some embodiments, the display device includes at least one red conversion layer, at least one green conversion layer, and at least one blue conversion layer.

[0222] In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm, about 3 μm to about 8 μm, about 3 μm to about 6 μm, about 6 μm to about 10 μm, about 6 μm to about 8 μm, or about 8 μm to about 10 μm. In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm.

[0223] The nanostructure color conversion layer can be deposited by any suitable method known in the art, including but not limited to painting, spraying, solvent spraying, wet coating, adhesive coating, spin coating, tape coating, roller coating, flow coating, inkjet printing, photoresist patterning, drop casting, blade coating, mist deposition, or a combination thereof. In some embodiments, the nanostructure color conversion layer is deposited by photoresist patterning. In some embodiments, the nanostructure color conversion layer is deposited by inkjet printing.

[0224] Inkjet Printing

[0225] The formation of thin films using dispersions of nanostructures in organic solvents is usually achieved by coating techniques such as spin coating. However, these coating techniques are generally not suitable for forming thin films over large areas, and do not provide methods for patterning deposited layers, so their uses are limited. Inkjet printing allows for accurate patterning of thin films on a large scale at low cost. Inkjet printing also allows for accurate patterning of nanostructure layers, allowing pixels of printed displays, and eliminating light patterning. Therefore, inkjet printing is very attractive for industrial applications, especially in display applications.

[0226] Solvents commonly used in inkjet printing are dipropylene glycol monomethyl ether acetate (DPMA), polyglycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC) and propylene glycol methyl ether acetate (PGMEA). Volatile solvents are also often used in inkjet printing because they allow fast drying. Volatile solvents include ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate and tetrahydrofuran. Conventional nanostructures are usually not dissolved in these solvents. However, the hydrophilicity of the increase of the nanostructure including the poly (alkylene oxide) ligand allows the solubility increased in these solvents.

[0227] In some embodiments, the nanostructures for inkjet printing described herein are dispersed in a solvent selected from DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, chloroform, chlorobenzene, cyclohexane, hexane, heptane, octane, hexadecane, undecane, decane, dodecane, xylene, toluene, benzene, octadecane, tetradecane, butyl ether, or a combination thereof. In some embodiments, the nanostructures comprising poly(alkylene oxide) ligands for inkjet printing described herein are dispersed in a solvent selected from DPMA, PGMA, EDGAC, PGMEA, ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, tetrahydrofuran, or a combination thereof.

[0228] For application by inkjet printing or microdispensing, the inkjet composition comprising the nanostructures should be dissolved in a suitable solvent. The solvent must be capable of dispersing the nanostructure composition and must not have any deleterious effects on the selected print head.

[0229] In some embodiments, the inkjet composition further includes one or more additional components, such as surfactant compounds, lubricants, wetting agents, dispersants, hydrophobic agents, binders, flow improvers, defoamers, deaerators, diluents, adjuvants, colorants, dyes, pigments, sensitizers, stabilizers, and inhibitors.

[0230] In some embodiments, the nanostructure compositions described herein comprise from about 0.01% to about 20% by weight of the inkjet composition. In some embodiments, the nanostructures comprising poly(alkylene oxide) ligands comprise from about 0.01% to about 20%, from about 0.01% to about 15%, from about 0.01% to about 10%, from about 0.01% to about 5%, from about 0.01% to about 2%, from about 0.01% to about 1%, from about 0.01% to about 0.1%, from about 0.01% to about 0.05%, from about 0.05% to about 20%, from about 0.05% to about 15%, from about 0.05% to about 5%, from about 0.05% to about 2%, from about 0.05% to about 1%, from about 0.05% to about 0.1%, from about 0.1% to about 20%, from about 0.1% to about 10%, from about 0.1% to about 5%, from about 0.1% to about 2%, from about 0.5% to about 20% by weight of the inkjet composition. About 0.5% and about 15%, about 0.5% and about 10%, about 0.5% and about 5%, about 0.5% and about 2%, about 0.5% and about 1%, about 1% and about 20%, about 1% and about 15%, about 1% and about 10%, about 1% and about 5%, about 1% and about 2%, about 2% and about 20%, about 2% and about 10%, about 2% and about 5%, about 5% and about 20%, about 5% and about 15%, about 5% and about 10%, about 10% and about 20%, about 10% and about 15%, or about 15% and 20%.

[0231] In some embodiments, the inkjet composition comprising the nanostructures or nanostructure compositions described herein is used to formulate an electronic device. In some embodiments, the inkjet composition comprising the nanostructures or nanostructure compositions described herein is used in the formulation of an electronic device selected from the group consisting of nanostructure films, display devices, light-emitting devices, backlight units, color filters, surface light-emitting devices, electrodes, magnetic storage devices, and batteries. In some embodiments, the inkjet composition comprising the nanostructure compositions described herein is used in the formulation of light-emitting devices.

[0232] lighting fixtures

[0233] In some embodiments, nanoparticles comprising zinc oxide can be used in an electron transport layer of a lighting device.

[0234] The lighting device can be used in a variety of applications, such as flexible electronics, touch screens, monitors, televisions, mobile phones, and any other high-definition displays. In some embodiments, the lighting device is a light emitting diode. In some embodiments, the lighting device is a quantum dot light emitting diode (QD-LED). An example of a QD-LED is disclosed in U.S. Patent Application No. 15 / 824,701, the entire contents of which are incorporated herein by reference.

[0235] In some embodiments, the present disclosure provides a lighting device, the lighting device comprising:

[0236] (a) a first conductive layer;

[0237] (b) a second conductive layer; and

[0238] (c) an emissive layer, wherein the emissive layer comprises at least one population of nanoparticles comprising a core and at least one shell disposed on the core, wherein the at least one shell comprises zinc and a Group IV metal fluoride.

[0239] In some embodiments, the lighting device comprises:

[0240] (a) a first conductive layer;

[0241] (b) a second conductive layer;

[0242] (c) an electron transport layer, wherein the electron transport layer comprises a population of at least one nanostructure;

[0243] (d) an emissive layer, wherein the emissive layer comprises at least one population of nanoparticles comprising a core comprising zinc and at least one shell, wherein at least one shell comprises zinc and a Group IV metal fluoride.

[0244] In some embodiments, the nanostructures are quantum dots.

[0245] In some embodiments, the lighting device includes a first conductive layer, a second conductive layer, and an electron transport layer, wherein the electron transport layer is disposed between the first conductive layer and the second conductive layer. In some embodiments, the electron transport layer is a thin film.

[0246] In some embodiments, the lighting device includes additional layers between the first conductive layer and the second conductive layer, such as a hole injection layer, a hole transport layer, an electron transport layer, and an emission layer. In some embodiments, the hole injection layer, the hole transport layer, the electron transport layer, and the emission layer are thin films. In some embodiments, these layers are stacked on a substrate.

[0247] When a voltage is applied to the first conductive layer and the second conductive layer, holes injected into the first conductive layer move to the emission layer via the hole injection layer and / or the hole transport layer, and electrons injected from the second conductive layer move to the emission layer via the electron transport layer. Holes and electrons recombine in the emission layer to generate excitons.

[0248] Substrate

[0249] The substrate can be any substrate commonly used to manufacture lighting devices. In some embodiments, the substrate is a transparent substrate, such as glass. In some embodiments, the substrate is a flexible material such as polyimide, or a flexible transparent material such as polyethylene terephthalate. In some embodiments, the thickness of the substrate is between about 0.1 mm and about 2 mm. In some embodiments, the substrate is a glass substrate, a plastic substrate, a metal substrate, or a silicon substrate.

[0250] First conductive layer

[0251] In some embodiments, the first conductive layer is disposed on a substrate. In some embodiments, the first conductive layer is a stack of conductive layers. In some embodiments, the thickness of the first conductive layer is between about 50 nm and about 250 nm. In some embodiments, the first conductive layer is deposited as a thin film using any known deposition technique, such as sputtering or electron beam evaporation. In some embodiments, the first conductive layer includes indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), zinc oxide (ZnO), magnesium (Mg), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag), silver (Ag), gold (Au) or a mixture thereof. In some embodiments, the first conductive layer is an anode.

[0252] Second conductive layer

[0253] In some embodiments, the additional layer can be sandwiched between the first conductive layer and the second conductive layer. In some embodiments, the first conductive layer is used as the anode of the device, and the second conductive layer is used as the cathode of the device. In some embodiments, the second conductive layer is a metal, such as aluminum. In some embodiments, the thickness of the second conductive layer is about 100nm to about 150nm. In some embodiments, the second conductive layer represents a stack of conductive layers. For example, the second conductive layer can include a silver layer sandwiched between two layers of ITO (ITO / Ag / ITO).

[0254] In some embodiments, the second conductive layer includes indium tin oxide (ITO), an alloy of indium oxide and zinc (IZO), titanium dioxide, tin oxide, zinc sulfide, silver (Ag), or a mixture thereof.

[0255] Semiconducting polymer layer

[0256] In some embodiments, the lighting device further comprises a semiconducting polymer layer. In some embodiments, the semiconducting polymer layer serves as a hole injection layer. In some embodiments, the semiconducting polymer layer is deposited on the first conductive layer. In some embodiments, the semiconducting polymer layer is deposited by vacuum deposition, spin coating, printing, casting, slot die coating or Langmuir-Blodgett (LB) deposition method. In some embodiments, the thickness of the semiconducting polymer layer is about 20nm to about 60nm.

[0257] In some embodiments, the semiconducting polymer layer includes copper phthalocyanine, 4,4',4"-tris[(3-methylphenyl)phenylamino]triphenylamine (m-MTDATA), 4,4',4"-tris(diphenylamino)triphenylamine (TDATA), 4,4',4"-tris[2-naphthyl(phenyl)amino]triphenylamine (2T-NATA), polyaniline / dodecylbenzenesulfonic acid, poly(3,4-ethylenedioxythiophene) / polystyrenesulfonate (PEDOT / PSS), polyaniline / camphorsulfonic acid, or polyaniline / poly(4-styrenesulfonate).

[0258] First transport layer

[0259] In some embodiments, the lighting device further comprises a transport layer to facilitate the transport of electrons and holes affected by the electric field generated between the first conductive layer and the second conductive layer. In some embodiments, the lighting device further comprises a first transport layer associated with the first conductive layer. In some embodiments, the first transport layer acts as a hole transport layer (and an electron and / or exciton blocking layer). In some embodiments, the first transport layer is deposited on the first conductive layer. In some embodiments, the first transport layer is deposited on the semiconductor polymer layer. In some embodiments, the thickness of the first transport layer is between about 20 nm and about 50 nm. In some embodiments, the first transport layer is substantially transparent to visible light.

[0260] In some embodiments, the first transmission layer comprises a material selected from an amine, a triarylamine, a thiophene, a carbazole, a phthalocyanine, a porphyrin, or a mixture thereof. In some embodiments, the first transmission layer comprises N,N'-di(naphthalene-1-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl))diphenylamine)] and poly(9-vinylcarbazole).

[0261] Second transport layer

[0262] In some embodiments, the lighting device further comprises a second transport layer. In some embodiments, the second transport layer acts as an electron transport layer (and hole and / or exciton blocking layer). In some embodiments, the second transport layer contacts the emissive layer. In some embodiments, the second transport layer is disposed between the emissive layer and the second conductive layer. In some embodiments, the thickness of the second transport layer is about 20 nm to about 50 nm. In some embodiments, the second transport layer is substantially transparent to visible light.

[0263] In some embodiments, the second transport layer is an electron transport layer.

[0264] When the polarities of the first conductive layer and the second conductive layer are reversed, the roles of the first transmission layer and the second transmission layer are reversed.

[0265] Electron transport layer

[0266] In some embodiments, the lighting device includes at least one electron transport layer. In some embodiments, the lighting device is a quantum dot light emitting diode.

[0267] In some embodiments, the thickness of the electron transport layer is from about 20 nm to about 50 nm. In some embodiments, the thickness of the electron transport layer is from about 20 nm to about 50 nm, from about 20 nm to about 40 nm, from about 20 nm to about 30 nm, from about 30 nm to about 50 nm, from about 30 nm to about 40 nm, or from about 40 nm to about 50 nm.

[0268] In some embodiments, the electron transport layer comprises zinc oxide. In some embodiments, the electron transport layer comprises zinc magnesium oxide.

[0269] Lighting device with improved performance

[0270] In some embodiments, the lighting device prepared using the nanostructures of the present disclosure exhibits an EQE of about 1.5% to about 20%, about 1.5% to about 15%, about 1.5% to about 12%, about 1.5% to about 10%, about 1.5% to about 8%, about 1.5% to about 4%, about 1.5% to about 3%, about 3% to about 20%, about 3% to about 15%, about 3% to about 10%, about 3% to about 8%, about 8% to about 20%, about 8% to about 15%, about 8% to about 12%, about 8% to about 10%, about 10% to about 20%, about 10% to about 15%, about 10% to about 12%, about 12% to about 20%, about 12% to about 15%, or about 15% to about 20%. In some embodiments, the lighting device prepared using the nanostructures of the present disclosure exhibits an EQE of about 2% to about 6%. In some embodiments, the lighting device is a light emitting diode.

[0271] In some embodiments, lighting devices prepared using the nanostructures of the present disclosure show improved lifetime. In some embodiments, lighting devices prepared using the nanostructures of the present disclosure achieve 500 nits (cd / m 2 ) to 50% of the initial brightness (T 50 ) for a period of about 1 second to about 100 seconds, about 1 second to about 60 seconds, about 1 second to about 40 seconds, about 1 second to about 30 seconds, about 1 second to about 20 seconds, about 1 second to about 10 seconds, about 10 seconds to about 100 seconds, about 10 seconds to about 60 seconds, about 10 seconds to about 40 seconds, about 10 seconds to about 30 seconds, about 10 seconds to about 20 seconds, about 20 seconds to about 100 seconds, about 20 seconds to about 50 seconds, about 20 seconds to about 40 seconds, about 20 seconds to about 30 seconds, about 30 seconds to about 40 seconds, about 40 seconds to about 100 seconds, about 40 seconds to about 60 seconds, or about 60 seconds to about 100 seconds. In some embodiments, a lighting device prepared using the nanostructures of the present disclosure reaches 500 nits (cd / m 2 ) to 50% of the initial brightness (T 50 ) for a period of between about 20 seconds and about 60 seconds.

[0272] Example

[0273] The following examples are illustrative and non-limiting of the products and methods described herein. Appropriate modifications and adjustments of the various conditions, formulations and other parameters commonly encountered in the art, as well as modifications and adjustments that are obvious to those skilled in the art based on this disclosure, are within the spirit and scope of the present invention.

[0274] Example 1

[0275] Synthesis of ZnSe using TOPTe precursor 1-x Te x Nanocrystals

[0276] Preparation of TOPTe precursor: A Te precursor mixture was prepared by first diluting trioctylphosphine telluride (1 MTe, ​​230 μL) with 2.5 mL of dried and distilled oleylamine. To this solution was added lithium triethylborohydride (1 M in THF, 230 μL) to give a dark purple solution. Finally, zinc oleate (0.5 M in trioctylphosphine (TOP), 460 μL) was added to give a colorless, opaque, viscous gel that could be drawn into a syringe.

[0277] Oleylamine (15mL) was added to a 100mL three-necked flask and vacuum degassed at 110°C for 30 minutes. The mixture was then heated to 300°C under a nitrogen stream. Once the temperature was reached, trioctylphosphine selenide (TOPSe, 2.7mmol) and diphenylphosphine (225μL) solution in TOP (2.9mL in total) were added to the flask. Once the temperature rebounded to 300°C, the above-mentioned TOPTe precursor and diethylzinc (295μL) solution in TOP (1mL) were quickly injected from different syringes. The temperature was set to 280°C, and after 5 minutes, diethylzinc (294μL) and TOPSe (4.4mmol) solutions in TOP (3.8mL in total) were injected at a rate of 0.5mL / min until all 3.8mL solutions were added. After the precursor injection was completed, the reaction mixture was kept at 280°C for 5 minutes and then cooled to room temperature. The growth solution was diluted with an equal volume of toluene (40 mL) and the nanocrystals were precipitated by adding ethanol (120 mL). After centrifugation, the supernatant was discarded and the nanocrystals were redispersed in hexane (5 mL). The concentration as dry weight was measured by evaporating the solvent from the aliquot. The dried material was further subjected to thermogravimetric analysis to determine the ZnSe content.

[0278] Example 2

[0279] Synthesis of ZnSe Nanocrystals

[0280] ZnSe nanocrystals were prepared using the method of Example 1 without injecting TOPTe precursor.

[0281] Example 3

[0282] ZnSe 1-x Te x Synthesis of ZnSe nanocrystals

[0283] Preparation of ZnSe with an average diameter of 4.0 nm and a target shell thickness of 4 monolayers (ML) of ZnSe 1-x Te x ZnSe buffer layer on nanocrystals.

[0284] Zinc oleate (6.23 g), lauric acid (3.96 g), trioctylphosphine oxide (4.66 g) and TOP (9.4 mL) were charged into a 100 mL three-necked flask. The flask was subjected to three cycles of vacuum and nitrogen backfilling, then heated to 100 ° C and degassed for 30 minutes. The reaction mixture was placed under a nitrogen blanket and ZnSe 1-x Te xA solution of core (4.0 mL, 28.0 mg / mL in hexane) mixed with TOPSe (1.8 mL, 0.3 M selenium in TOP) was added to a flask. The flask was evacuated for 2 minutes and then heated to 310°C under a nitrogen stream. Once the temperature was reached, TOPSe (10.4 mL, 0.3 M in TOP) was slowly injected at a rate of 0.325 mL / min. After the selenium injection was completed, the reaction was kept at 310°C for 10 minutes and then cooled to room temperature. The reaction mixture was diluted with toluene (45 mL). The core / shell nanocrystals were precipitated by adding ethanol (135 mL), then separated by centrifugation, the supernatant was decanted, and the nanocrystals were redispersed in hexane (5 mL). The solution was filtered through a PTFE 0.22 μm syringe filter and the concentration was measured by dry weight by evaporating the solvent from an aliquot. The dried material was further subjected to thermogravimetric analysis to determine the ZnSe content.

[0285] Example 4

[0286] Synthesis of ZnSe / ZnS Nanocrystals

[0287] A ZnS buffer layer on ZnSe nanocrystals with an average diameter of 4.0 nm and a target shell thickness of 4 monolayers (ML) of ZnS was prepared.

[0288] Zinc oleate (27.63g), lauric acid (17.54g), trioctylphosphine oxide (18.00g) and TOP (36.0mL) are loaded into a 500mL three-necked flask. The flask is then subjected to three vacuum and nitrogen backfill cycles, then heated to 100°C and degassed for 30 minutes. The reaction mixture is placed under a nitrogen blanket, and ZnSe core solution (2.0mL, 216.0mg / mL, in hexane) is added to the flask. The flask is evacuated for 2 minutes, and then heated to 310°C under a nitrogen stream. Once the temperature is reached, TOPS (25.3mL of 2.0M sulfur in TOP) is slowly injected at a rate of 0.720mL / min. After sulfur injection ends, the reaction is kept at 310°C for 10 minutes, then cooled to room temperature. The reaction mixture is diluted with toluene (95mL). The core / shell nanocrystals were precipitated by adding ethanol (190 mL) and then separated by centrifugation, the supernatant was decanted, and the nanocrystals were redispersed in hexane (7 mL). The solution was filtered through a PTFE 0.22 μm syringe filter and the concentration was measured by evaporating the solvent from an aliquot as dry weight.

[0289] Example 5

[0290] ZnSe 1-x Te x Synthesis of ZnSe / ZnS Nanocrystals

[0291] ZnSe with an average diameter of 6.1 nm and a target shell thickness of 4 monolayers (ML) of ZnS were prepared. 1-x Te x / ZnS shell on ZnSe nanocrystals.

[0292] Zinc oleate (375 mg), lauric acid (240 mg), trioctylphosphine oxide (281 mg) and TOP (0.566 mL) were charged into a 25 mL three-necked flask. The flask was then subjected to three vacuum and nitrogen backfill cycles, then heated to 100° C. and degassed for 30 minutes. The reaction mixture was placed under a nitrogen blanket, and ZnSe mixed with zinc oleate / TOPS (0.064 ml of 2.0 M sulfur in TOP + 0.254 ml of 0.5 M zinc oleate in TOP) was added to the flask. 1-x Te x The core / shell nanocrystals were precipitated by adding ethanol (10 mL), and then the supernatant was decanted by centrifugation, and the nanocrystals were redispersed in hexane (5 mL). The precipitation was repeated once with ethanol (10 mL), and finally the nanocrystals were redispersed in octane (3 mL). The solution was filtered through a PTFE 0.22 μm syringe filter and the concentration was adjusted to 18 mg / mL after measuring the dry weight of the aliquot.

[0293] Example 6

[0294] Synthesis of ZnSe / ZnS Nanocrystals with Hafnium Fluoride Passivation

[0295] The procedure was the same as outlined in Example 4, except that the flask was also charged with anhydrous hafnium fluoride (242 mg) prior to the initial three cycles of vacuum and nitrogen backfill.

[0296] Example 7

[0297] Synthesis of ZnSe / ZnS Nanocrystals Passivated with Zirconium Fluoride

[0298] The procedure was the same as outlined in Example 4, except that the flask was also charged with anhydrous zirconium fluoride (159 mg) prior to the initial three cycles of vacuum and nitrogen backfill.

[0299] Example 8

[0300] ZnSe with Hafnium Fluoride Passivation 1-x Te x Synthesis of ZnSe / ZnS Nanocrystals

[0301] The procedure was the same as outlined in Example 5, except that the flask was also charged with anhydrous hafnium fluoride (251 mg) prior to the initial three cycles of vacuum and nitrogen backfill.

[0302] Example 9

[0303] Photoluminescent properties of nanocrystals prepared using Group IV fluorides

[0304] ZnSe / ZnS core / shell and ZnSe prepared in the presence of Group IV fluorides 1-x Te x The solution photoluminescence spectra of ZnSe / ZnS core / shell / shell quantum dots are shown in Table 1. As shown in Table 1, the obtained core / shell quantum dots with a well-passivated surface exhibit high quantum yield (QY) and narrow full width at half maximum (FWHM).

[0305] The incorporation of Group IV fluorides during shell growth also results in a change in the morphology of quantum dots with ZnS shells. Instead of the quasi-spherical particles ( Figure 3 and Figure 5 ), in the presence of HfF4, particles with a cubic shape were obtained ( Figure 4 and Figure 6 ).

[0306] Table 1

[0307]

[0308] Example 10

[0309] Electroluminescent devices using nanocrystals prepared with Group IV metal fluorides

[0310] The devices were prepared by a combination of spin coating and thermal evaporation. First, the hole injection material poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) (50 nm) was spin coated onto a UV-ozone treated indium tin oxide (ITO) substrate and baked at 200°C for 15 min. The device was transferred to an inert atmosphere and the hole transport material N,N'-di(naphthalene-1-yl)-N,N'-bis(4-vinylphenyl)biphenyl-4,4'-diamine (VNPB) (20 nm) was deposited by spin coating and baked at 200°C for 15 min. ZnSe / ZnS or ZnSe was deposited by spin coating (no resin was used in the emissive layer). 1-x Te x / ZnSe / ZnS QDs were prepared by spin coating the electron transport material ZnMgO (20 nm). An Al cathode (150 nm) was then deposited by thermal evaporation, followed by encapsulation of the device using a cover glass, getter, and epoxy resin.

[0311] In an electrochemical device, the cubic particles were found to have significantly less attenuation at higher luminescence ( Figure 7 ). This improved attenuation indicates that the Group IV metal fluoride ligands have improved surface passivation and electrochemical stability.

[0312] Embodiment 11

[0313] Performance of the prepared electroluminescent device

[0314] ZnSe / ZnS core / shell and ZnSe prepared in the presence of Group IV metal fluoride 1-x Te x The electroluminescence spectra of the device with ZnSe / ZnS core / shell / shell quantum dots are shown in Table 2. As shown in Table 2, in the quantum dots prepared in the presence of Group IV metal fluorides, the electroluminescence lifetime (at 500 cd / m 2 T 50 ) increased by 2-3 times.

[0315] Table 2

[0316]

[0317] Furthermore, evidence of hole trap passivation can be observed in hole-only devices made with Group IV metal fluorides ( Figure 8 ). Keeping the hole current (0.1J) and thickness equal, as shown by comparing the output voltage (V o ) and forward voltage (V f ), the use of nanostructures prepared with Group IV metal fluorides requires a lower (60-80 mV less) voltage to deliver the applied current. In addition, it was found that the voltage rise (dV / dt) was lower (9-12%) during the test, as shown in Table 3. This provides direct evidence of the improvement in hole conductivity due to the increase in hole trap passivation.

[0318] Table 3

[0319]

[0320] Although various embodiments have been described above, it should be understood that they are presented as examples rather than limitations. It will be apparent to those skilled in the relevant art that various changes may be made in form and detail without departing from the spirit and scope of the present invention. Therefore, the breadth and scope should not be limited by any of the above exemplary embodiments, but should only be limited according to the attached claims and their equivalents.

[0321] All publications, patents, and patent applications mentioned in this specification are indicative of the levels of skill of those skilled in the art to which this invention pertains, and are incorporated herein by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference.

Claims

1. A nanostructure comprising a nanocrystalline core and at least one shell, wherein at least one shell comprises at least one metal fluoride as shown in formula (I): MF4(I) in: M=Zr, Hf or Ti, Wherein the core comprises ZnSe or ZnSe 1-x Te x , where 0≤x<1, at least one shell comprises ZnSe or ZnS, And the nanostructure has a size less than 20 nm.

2. The nanostructure according to claim 1, wherein the at least one metal fluoride is HfF4 or ZrF4.

3. The nanostructure according to any one of claims 1 or 2, wherein in the nanostructure, the molar ratio of at least one metal fluoride to zinc is 1:1 to 1:

8.

4. The nanostructure according to any one of claims 1 or 2, wherein the nanostructure comprises: (a) a core comprising ZnSe, at least one shell comprising ZnS and at least one shell comprising HfF4; or (b) Containing ZnSe 1-x Te x A core wherein 0≤x<1, at least one shell comprising ZnSe, and at least one shell comprising ZnS, and at least one shell comprising HfF4.

5. The nanostructure according to any one of claims 1 or 2, wherein the nanostructure is a quantum dot.

6. The nanostructure according to any one of claims 1 or 2, wherein the photoluminescence quantum yield of the nanostructure is 60% to 100%. 7 . The nanostructure according to claim 1 , wherein the full width at half maximum of the nanostructure is from 10 nm to 40 nm.

8. A nanostructured composition comprising: (a) a nanostructure according to any one of claims 1 to 7; and (b) at least one organic resin.

9. A method for preparing the nanostructure according to any one of claims 1 to 7, comprising: (a) providing a nanocrystal core; (b) optionally mixing the core of (a) with a zinc source and a selenium source to provide a core having a ZnSe shell; (c) mixing the core in (a) or the core with a ZnSe shell in (b) with a zinc source, a sulfur source and at least one metal fluoride of formula (I): MF4(I) in: M=Zr, Hf or Ti; To provide the nanostructure.

10. The method according to claim 9, wherein the zinc source in (b) is selected from diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or a mixture thereof.

11. The method according to claim 9, wherein the zinc source in (c) is selected from diethyl zinc, dimethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oleate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, zinc hexanoate, zinc octoate, zinc laurate, zinc myristate, zinc palmitate, zinc stearate, zinc dithiocarbamate or a mixture thereof.

12. The method according to claim 9, wherein the selenium source in (b) is selected from trioctylphosphine selenide, tri(n-butyl)phosphine selenide, tri(sec-butyl)phosphine selenide, tri(tert-butyl)phosphine selenide, trimethylphosphine selenide, triphenylphosphine selenide, diphenylphosphine selenide, phenylphosphine selenide, tricyclohexylphosphine selenide, cyclohexylphosphine selenide, 1-octane selenol, 1-dodecane selenol, selenophene, elemental selenium, hydrogen selenide, bis(trimethylsilyl)selenide, selenourea and combinations thereof.

13. The method according to claim 9, wherein the sulfur source in (c) is selected from elemental sulfur, octyl mercaptan, dodecanethiol, octadecyl mercaptan, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluene mercaptan, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide and combinations thereof.

14. The method according to claim 9, wherein the temperature in (b) is increased, decreased or maintained at 200°C to 310°C.

15. The method of claim 9, wherein the temperature in (c) is increased, decreased or maintained at 280°C to 310°C.

16. The method of claim 9, wherein the photoluminescence quantum yield of the nanostructure is 60% to 100%. The method according to claim 9 , wherein the full width at half maximum of the nanostructure is 10 nm to 40 nm.

18. A lighting device, comprising: (a) a first conductive layer; (b) a second conductive layer; and (c) An emitting layer, wherein the emitting layer comprises at least one nanostructure population according to any one of claims 1 to 7.

19. The lighting device of claim 18, wherein the at least one metal fluoride of the nanostructure is HfF4 or ZrF4.

20. The lighting device of claim 18, wherein the device is stable for at least 7 days when stored at room temperature.

21. The lighting device of claim 18, wherein the device is stable for at least 14 days when stored at room temperature.

22. The lighting device according to claim 18, further comprising an electron transport layer.

23. The lighting device of claim 18, wherein the lighting device is a light emitting diode.

24. The lighting device of claim 18, wherein the first conductive layer comprises indium tin oxide, indium zinc oxide, tin dioxide, zinc oxide, magnesium, aluminum, aluminum-lithium, calcium, magnesium-indium, magnesium-silver, silver, gold, or a mixture thereof.

25. The lighting device of claim 18, wherein the first conductive layer comprises indium tin oxide. 26 . The lighting device of claim 18 , wherein the second conductive layer comprises indium tin oxide, indium zinc oxide, titanium dioxide, tin oxide, zinc sulfide, silver, or a mixture thereof.

27. The lighting device of claim 18, wherein the second conductive layer comprises aluminum.

28. The lighting device of claim 18, wherein the second conductive layer comprises gold.

29. The lighting device of claim 18, further comprising a semiconducting polymer layer.

30. The lighting device of claim 29, wherein the semiconductor polymer layer comprises copper phthalocyanine, 4,4',4"-tris[(3-methylphenyl)phenylamino]triphenylamine (m-MTDATA), 4,4',4"-tris(diphenylamino)triphenylamine (TDATA), 4,4',4"-tris[2-naphthyl(phenyl)amino]triphenylamine (2T-NATA), polyaniline / dodecylbenzenesulfonic acid, poly(3,4-ethylenedioxythiophene) / polystyrenesulfonate (PEDOT / PSS), polyaniline / camphorsulfonic acid, or polyaniline / poly(4-styrenesulfonate).

31. The lighting device of claim 29 or 30, wherein the semiconducting polymer layer comprises PEDOT / PSS.

32. The lighting device of claim 18, further comprising a first transmission layer.

33. The illumination device of claim 32, wherein the first transmission layer comprises N,N'-di(naphthalen-1-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine, poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl))diphenylamine)], or poly(9-vinylcarbazole).

34. The lighting device of claim 32 or 33, wherein the first transmission layer comprises N,N'-di(naphthalen-1-yl)-N,N'-bis(4-vinylphenyl)-4,4'-diamine.

Citation Information

Patent Citations

  • Quantum dot LED with spacer particles

    US10790411B2

  • Quantum dot color filter and display apparatus including the same

    US20170153366A1

  • Blue-emitting nanocrystals with cubic shape and fluoride passivation

    US20210009900A1